P5.064 Preliminary Analytical Evaluation of Artus® CT/NG, For Simultaneous Detection of Neisseria Gonorrhoeae and Chlamydia Trachomatis. (13th July 2013) - Tabrizi, S N; Twin, J; Unemo, M; Wiezer, A; Limnios, A; Lahra, M; Garland, S
Abstract : Introduction: Currently there are a number of molecular amplification assays for detection of Neisseria gonorrhoeae and Chlamydia trachomatis . Prior to introduction of any new assay, it should be thoroughly evaluated for potential false positive and false negative results due to cross reaction with other species, and potential mutations and genetic exchanges with other closely related organisms. Artus ® CT/NG is currently a research use only kit (with the fully automated version to be released later this year)for simultaneously detection of C. trachomatis and N. gonorrhoeae . We performed preliminary analytical evaluation of this assay. Method: This study evaluated the Artus ® CT/NG assay with 290 characterised culture isolates obtained from the Neisseria Reference Laboratory at the World Health Organization Collaborating Centres for Sexually Transmitted Disease (STD) in Sydney and WHO Collaborating Centre for Gonorrhoea and other STIs in Örebro, Sweden. Strains included 148 N. gonorrhoeae isolates, 130 isolates of non-gonococcal Neisseria species, 12 isolates of other species closely related to Neisseria and 16 C. trachomatis strains of different serovars (including LGV and nvCT strains). Results: All C. trachomatis and N. gonorrhoeae isolates were detected. A detection sensitivity of 10 genome copies per reaction was obtained with all C. trachomatis serovars as well as a representative N. gonorrhoeae control strain. All 142 non-gonococcal isolates were negative on the assay. Conclusion: Overall, from this limited evaluation, Artus ® CT/NG is analytically highly sensitive and specific for the detection of C. trachomatis and N. gonorrhoeae . Further assessment with clinical samples would need to be done to fully assess the performance of this assay prior to clinical implementation.